An Informal Representation of the Language Spoken by Children from the Nias Ethnic Group in Banuaran - Nazara Nazara; Wa’özisökhi Nazara; Oktavianus Oktavianus (STBA Prayoga Padang, 2017)
This research aims to identify the language used by children from Nias ethnic families in Banuaran as well as the reason for using the language. The writers wanted to know what language is used and the possible use of other languages and code-mixing performed by these children in various situations, including athome, in the community of Nias, and in other places. The authors would like to know the reason of the selection and use of the language. The authors used andpresented the analysis based on the data obtained is descriptive. The authors conducted observations on the use of language by children at home and in thecommunity of Nias Banuaran Family Association (IKNB). The authors uses several instruments in retrieving data in the form of recordings and thequestioner to be filled by children and parents. It was found that children from the Nias ethnic group in Banuaran use Indonesian and Minangkabau language.They use the languages due to neighborhood environment, family condition, and negative perception on Nias ethnic group. This reveals that the children‟slanguage choice is functional/motivated.